English as a Foreign Language Learners’ Academic Achievement: Does Creativity and Self-Efficacy Matter? - Wang, Shanshan; Chen, Yaling; Wan, Yi (Frontiers in Psychology, 2022)
Given the centrality of learners’ individual differences in their academic achievement, a plethora of research has been done on various individual difference variables and their associations with learners’ increased achievement. Yet, the role of creativity and self-efficacy in EFL learners’ academic achievement has not been extensively studied. Further, no review inquiry has simultaneously probed into the consequences of these two individual difference variables for learners’ academic achievement. This study strives to fill this underappreciated gap by addressing the positive consequences of creativity and self-efficacy for EFL learners’ academic achievement. The desirable consequences of creativity and self-efficacy beliefs were clarified using the available evidence. Finally, the conclusions and consequences of the findings are discussed.